Frankfurt am Main/Mainz, Deutschland. Spuren archäologischer Wissensgenerierung. Propylaeum-VITAE, ein von der DFG gefördertes Verbundprojekt zur archäologischen Wissenschaftsgeschichte - Rasbach, Gabriele; Schröer, Sandra; Hofman, Kerstin P.; Frey, Annette; Berbüsse, Constanze; Effinger, Maria; Grunwald, Susanne; Merten, Jürgen (e-Forschungsberichte des DAI, 2021)
In 2017 the biographical information system Propylaeum-VITAE launched, which is hosted by the Specialist Information Service of Classics »Propylaeum« at the university library Heidelberg. The online database is a tool not only for researching biographical information of former scholars of classical studies, pre- and protohistory but also to analyse their personal networks, the generation of knowledge as well as the genesis and development of concepts and methods in classical studies. Based on this, in August 2020 the German Research Foundation approved a project, applied by the RGK, RGZM and Heidelberg University Library, called »Spuren Archäologischer Wissensgenerierung (Traces of archaeological knowledge)«. The project aims to expand Propylaeum-VITAE systematicaly and to index archival and bibliographical sources stored in the Archives and Libraries of the RGZM, RGK and further cooperation partners via the biographical information system.